مساهمة الرموز الثقافية للقبيلة في الحفاظ على الهوية الجزائرية خلال المرحلة الاستعمارية. - مرابطي, رفيقة (University of Eloued جامعة الوادي, 2022)
لم تكن القبيلة خلال الفترة الاستعمارية للجزائر مجرد فضاء جغرافي يضم مجموعة من الأفراد تجمعهم روابط مختلفة فحسب، بل شكلت الوعاء الذي حفظ للمجتمع سيرورته التاريخية وهويته الثقافية، نتيجة تكوينها القائم على الانتماء إلى الدين والتاريخ المشترك، وتطورها ضمن مجتمع تحكمه مقومات الوحدة والتماثل، ونظرا لبقائها بعيدة عن التأثيرات الثقافية للسياسة الاستعمارية خاصة في الأرياف، ظلت قوية التماسك بموروثها المحلي الذي طبع سلطتها المترسخة عبر الأجيال، وهو ما جعلها تقاوم كل ما هو دخيل عنها مهما كانت قوته. والإشكالية هنا تتمحور حول مدى أهمية القبيلة كوعاء اجتماعي حافظ للرموز الثقافية المكونة للهوية الجزائرية خلال مرحلة الاستعمار الفرنسي، لذلك نهدف إلى إبراز الخصوصيات التي ميزت المجتمع الجزائري ضمن فضاءه القبلي؟ وكيف استطاعت القبيلة المحافظة على المقومات الثقافية المشكلة للهوية الوطنية؟ During the colonial period of Algeria, the tribe was not just a geographical space comprising a group of individuals brought together by different ties, but it was the container that preserved the society’s historical process and cultural identity, as a result of its formation based on belonging to a religion and a common history. And its development within a society governed by the elements of unity and symmetry, and due to its staying away from the cultural influences of the colonial policy, especially in the countryside, it remained strongly cohesive with its local heritage, which marked its entrenched authority through generations, which made it resist everything that was foreign to it, no matter how strong it was. The problem here revolves around the extent of the importance of the tribe as a social container that preserves the cultural symbols that make up the Algerian identity during the French colonial period, so we aim to highlight the peculiarities that characterized Algerian society within its tribal space? And how was the tribe able to preserve the cultural components that formed the Algerian identity?
مقال